Association between dietary inflammatory index and cognitive impairment: A meta-analysis - Jia, Yuxi; Yan, Shoumeng; Sun, Mengzi; Yang, Yixue; Wang, Ling; Wu, Caihong; Li, Ping (Frontiers in Aging Neuroscience, 2023)
Aims: Cognitive impairment is an increasingly pressing public health problem worldwide. Dietary Inflammatory Index (DII) is a literature-derived score that links diet to inflammation. The relationship between DII and cognitive impairment remains controversial. Therefore, our study aimed to evaluate the role of DII on the risk of cognitive impairment by meta-analysis. Methods: PubMed, Cochrane Library, MEDLINE, Web of Science and EMBASE databases were searched up to July 2022. Newcastle–Ottawa scale (NOS) and Joanna Briggs Institute (JBI) Checklist were used to estimate the quality of studies. Results: Nine observational studies with 19379 subjects were included. Our study found that higher DII could increase the risk of cognitive impairment (OR =1.46, 95%CI=1.26, 1.69). Meanwhile, the OR of cognitive impairment was 1.49 (95%CI=1.21, 1.83) for cross-sectional studies and 1.42 (95%CI=1.12, 1.79) for cohort studies, respectively. Conclusions: Our meta-analysis indicated that higher DII (representing a more pro-inflammatory diet) is associated with increased risk of cognitive impairment.